Folk Cultural Consciousness in Hindi Literature: हिन्दी साहित्य मे लोक सांस्कृतिक चेतना - Meena, Bijendra Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In folk culture, the word culture functions as a qualifier, meaning that which is related to or associated with culture. Folk culture is a technical term formed by the combination of two words, folk and culture. The term folk, when used as a qualifier for culture, gives the word culture a meaning that is different and more specific than its general sense. Here, folk refers to that section of human society which remains free from the ego of scholasticism and lives within the continuous flow of tradition. Culture, in this context, is synonymous with a social practice that refines and enriches the collective personality of society. Abstract in Hindi Language: लोक-संस्कृति में संस्कृति शब्द विशेषण है, जिसका अर्थ है-संस्कृति से सम्बन्ध रखने वाला या संस्कृति सम्बन्धी। लोक-सांस्कृतिक एक परिभाषिक शब्द है, जो दो शब्दों ’लोक’ और ’संस्कृति’ के योग से बना है। लोक विशेषण से विशेषित संस्कृति’ शब्द का अर्थ ’संस्कृति’ के सामान्य अर्थ से भिन्न और विशिष्ट हें लोक जिसका अभिप्रेत मनुष्य समाज के उस वर्ग से है जो पांडित्य के अहम् से मुक्त परम्परा के प्रवाह में जीवित रहता है और संस्कृति एक ऐसी सामाजिक प्रथा का पर्याय है जो समाज के व्यक्तित्व को परिष्कृत एवम् समृद्ध बनाती है। Keywords: लोक-संस्कृति, पांडित्य, परिष्कृत, प्रतिबिम्बित, मानवता, अकथनीय, सामाजिक प्रथा